(untitled) (Intent Research Scientific Journal, 2023)
Man is comprehensively studied by the humanities. In psychology, a person is studied as a product of biological evolution, as the main driving force of society and its production, as a subject of production and other social relations. Due to the fact that the relationship of a person with other people and the outside world is diverse, the psychological qualities and qualities characteristic of him are extremely diverse. this article analyzes the main sensory characteristics of a person in the knowledge of the external world.